2022
DOI: 10.15170/ar.2022.7.1.3.
|View full text |Cite
|
Sign up to set email alerts
|

Lights and Shadows: The Inclusion of Invisible Students in Spanish Universities

Abstract: Spanish universities in the 21st century are a far cry from institutions prior to the 1970s, which were characterized by strong social homogeneity where only students who had to study did. In this elitist context, there was a direct correlation between social class and the education system (García de León & García de Cortázar, 1992). In recent decades, universities have grown to become more inclusive instead of only serving privileged members of society. This has led to a situation in which university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…They also believe that applying and becoming a member of the Roma student society is a sign of having a positive minority identity. Thus, in contrast to invisibility, as in the Spanish example [18], Roma student society members have a positive self-identification that is reinforced through membership.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…They also believe that applying and becoming a member of the Roma student society is a sign of having a positive minority identity. Thus, in contrast to invisibility, as in the Spanish example [18], Roma student society members have a positive self-identification that is reinforced through membership.…”
Section: Discussionmentioning
confidence: 97%
“…Research around the world is identifying new groups that have been underrepresented in higher education [16] and exploring ways to make institutions more inclusive [17]. Examining the Spanish higher educational setting, researchers have detected various student groups, highlighting that their heterogeneity manifests in diverse student needs [18]. Based on their interview research, they have found that these students need to overcome more difficulties, attempts at which are often not supported or recognized by the university; thus, they feel invisible [18].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudiar en la universidad es una oportunidad para mejorar las competencias personales y profesionales, beneficiarse de relaciones sociales o incrementar las posibilidades de obtener un empleo e independencia económica (Fernández-Batanero et al, 2022;Padilla et al, 2022;Rodríguez et al, 2021). De hecho, según la Comisión Europea (2022), los jóvenes adultos con títulos universitarios (entre 25 a 34 años) pueden ganar un 38 % más que sus iguales que únicamente han estudiado Educación secundaria.…”
Section: Revisión De Literaturaunclassified
“…Las universidades tienen la responsabilidad de repensar sus culturas, políticas y prácticas para que la inclusión sea real y que todas las personas, sin excepción, puedan sentirse realmente reconocidas y bienvenidas, aprendan, participen y tengan éxito (Koutsouris et al, 2022;Lourens y Swartz, 2019;Padilla et al, 2022). Sin embargo, los estudios revelan que las barreras aún persisten en la Educación Superior (Collins et al, 2018;González-Castellano et al, 2021;Medina-García et al, 2021).…”
Section: Revisión De Literaturaunclassified